Asian games ; Healing hands ; Yo, Francis [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1990)
Tackles the reasons of Philippine team making a poor show in the last Asian games; the traditional healing; and Francis Magallona punches messages through in his Mga Kababayan rap music for birds.
Asian Games (13 min.) -- Healing Hands (17 min.) -- Yo, Francis (12 min.)
VHS.
Keywords: Mgallona, Francis -- Interviews; Athletic ability -- Philippines; Hilots -- Philippines; Healers -- Philippines; Folk medicine -- Philippines